Extracellular vesicles mediate biological information delivery: A double-edged sword in cardiac remodeling after myocardial infarction - Cheng, Peipei; Wang, Xinting; Liu, Qian; Yang, Tao; Qu, Huiyan; Zhou, Hua (Frontiers in Pharmacology, 2023)
Acute myocardial infarction (AMI) is a severe ischemic disease with high morbidity and mortality worldwide. Maladaptive cardiac remodeling is a series of abnormalities in cardiac structure and function that occurs following myocardial infarction (MI). The pathophysiology of this process can be separated into two distinct phases: the initial inflammatory response, and the subsequent longer-term scar revision that includes the regression of inflammation, neovascularization, and fibrotic scar formation. Extracellular vesicles (EVs) are nano-sized lipid bilayer vesicles released into the extracellular environment by eukaryotic cells, containing bioinformatic transmitters which are essential mediators of intercellular communication. EVs of different cellular origins play an essential role in cardiac remodeling after MI. In this review, we first introduce the pathophysiology of post-infarction cardiac remodeling, as well as the biogenesis, classification, delivery, and functions of EVs. Then, we explore the dual role of these small molecule transmitters delivered by EVs in post-infarction cardiac remodeling, including the double-edged sword of pro-and anti-inflammation, and pro-and anti-fibrosis, which is significant for post-infarction cardiac repair. Finally, we discuss the pharmacological and engineered targeting of EVs for promoting heart repair after MI, thus revealing the potential value of targeted modulation of EVs and its use as a drug delivery vehicle in the therapeutic process of post-infarction cardiac remodeling.